The relationship between e-training, motivation and job performance during movement control order / Nur Atiqah Adnan and Shaiful Annuar Khalid - Adnan, Nur Atiqah; Khalid, Shaiful Annuar (Universiti Teknologi MARA, Kedah, 2021)
Covid19 pandemic which is spread almost all over the world has changed the pattern of human life, both economically and socially. As a result of Movement Control Order (MCO), organizations today are turning to online training involving staff at all levels. Although etraining is considered economical, certain methods and strategies need to be sought so that the effectiveness of e-training in enhancing employees' job performance can be achieved. This study is carried out to examine the relationship between several elements of training effectiveness and job performance. This study is cross-sectional and correlational in nature. Based on the data obtained from 140 empl oyees in a municipal council in Malaysia, regression analysis found that there is a significant relationship between e-training efficiencies, etraining method and training motivation with job performance. The results of this study provide implication to the organization in finding ways to increase the effectiveness of the implementation of e-training.